The Circus: memories of architecture in motion (Patrimônio e Memória, 2018)
The circus is a repository of meanings, images and representations, one of which is its nomadic architecture; a symbol of a traveling culture whose effectiveness consists of temporarily blending into the local landscape. Over time we have seen the construction of various styles of circus architecture which, on the one hand, seem to accompany the changes in the meaning of this culture, and on the other, reveal a unique way of inhabiting the world. Without claiming to be a history of the circus in Brazil, the analysis is based on circus memories recorded in written, oral and visual narratives, providing us with a panoramic view of circus architecture and shows in accordance with the environment and historical changes that took place throughout the 20th century.